The Effectiveness of Flipbook-Based Blanded Leaning Technology on Thinking Skills and Student Learning Outcomes - Mutiani, Mutiani; Syarifuddin, Syarifuddin; Syaharuddin, Syaharuddin; Hassan, Muhammad Ikram bin Abu; Jumriani, Jumriani; Nur’aini, Fatwa (International Journal of Social Learning (IJSL), 2024)
This study uses a quasi-experimental design to examine the effectiveness of a flipbook-based blended learning method on student learning outcomes at SMPN 3 Banjarmasin. Participants included an experimental group (n=30) utilizing the flipbook-based method and a control group (n=31) using traditional approaches. Pre-test and post-test assessments measured learning outcomes. Results showed that the experimental group significantly outperformed the control group, achieving an average post-test score of 85.97 compared to 75.90, with a mean difference of 10.06 (p < 0.001). ANCOVA analysis demonstrated the learning method's significant impact on post-test scores (F = 15.508, p < 0.001), independent of pre-test performance (F = 0.032, p = 0.860). Residual analysis raised concerns about the assumptions of linearity and normal distribution, warranting further validation of the model. The learning method accounted for 25% of post-test score variability, suggesting the influence of additional factors. These findings affirm the method's effectiveness and call for comprehensive model assessments in educational studies.